Physiological and epidemiological studies on Kala- azar disease in MissanGovernorate - Ali, Zainab (University of Thi-Qar Journal of Science, 2012)
The present study was made to known the effect of Kala-azar disease on some biochemical parameters in children. The GOT, GPT ALP, total protein and total bilirubin were measured in 50 infected children for both sex (21 male and 29 female). The research also included the study of (number of infected children and their ages during the 16 last year and months of year).The results showed significant increase (P<0.005)in male and high significant (P<0.005)in female in GOT in the infected children compared with health children .The value of GPT didn’t show significant differ in male ,but its show high significant increase (P<0.001) in the infected female.The value of ALP show significant increase (P<0.005) in infected male, while its value didn’t showsignificant different in female. The values of total protein and bilirubin don’t reach to significant level ininfected children compared with control. The percent of infection differ during the last 16 years ago. High percent in the infected male were record in 2007 (64%) and low percent in 1995 (41%), high percent of the infected female were record in 1995 (59%) and low percent in 2007 (36 %.) The age of children between 1-2 year recorded high number of infection about (961) case , while the age greater than 5 year recorded low number of infection ( 31) case. The month of year also effect on the number of infection, high percent of the infection were recorded during Jenuary (17.7%) and low percent in Augest (2.4%).